Cyclopropyl Containing Fatty Acids as Mechanistic Probes for Cytochromes P450 - Cryle, Max J; Ortiz de Montellano, Paul R; De Voss, James J (Journal of organic chemistry, 2005)
The mechanism of aliphatic hydroxylation by cytochromes P450 has been the subject of intense debate with several proposed mechanistic alternatives. Various cyclopropyl containing compounds (radical clocks), which can produce both unrearranged and ring opened products upon oxidation, have been key tools in these investigations. In this study, we introduce several cyclopropyl containing fatty acids 1a−4a with which to probe the mechanism of P450s capable of fatty acid hydroxylation. The probes are shown to be capable of distinguishing radical from cationic intermediates due to the rapid equilibration of isomeric cyclopropyl cations. Ring opening of a radical intermediate in an oxidative transformation is expected to yield a single rearranged alcohol, whereas a cation isomerizes prior to ring opening, leading to two isomeric homoallylic alcohols. Oxidation of these probes by P450BM3 and P450BioI gives results consistent with a radical but not a cationic intermediate in fatty acid hydroxylation by these enzymes. Quantitation of the unrearranged and ring opened products gives remarkably homogeneous rates for oxygen rebound of (2−3) × 1010 s-1. The effects of introduction of a cyclopropane ring into a fatty acid upon the regiochemistry of hydroxylation are discussed.